Design, Launch, and Scale IoT Services A Practical Business Approach - Haughian, Barry (Apress, 2018)
The Internet of Things is causing major industry disruption, so companies need to plan and manage their "IoT journey" to maximize all business opportunities. In this book companies can learn how to successfully create, launch and manage Internet of Things services. It takes the reader through the process of specifying, implementing, and deploying IoT services; detailing how to scale and manage an IoT business. It introduces the fundamentals of IoT services, explaining IoT service building blocks and the key factors to be considered in the design of IoT services. Moving into the IoT field requires speed. This book provides a fast track approach to IoT; summarizing the global experiences of the author, detailing the discussions, mistakes, successes, learnings and conclusions. Building an Internet of Things Service enables readers to accelerate their own on-boarding in their IoT journey.